A large-scale phylogeny of polygonaceae based on molecular data (2009)
Few studies have addressed the evolutionary relationships within Polygonaceae from a global perspective. The convoluted taxonomic history of Polygonaceae is a major barrier to understanding evolution in this group, and only portions of it have been included in systematic treatments. Phylogenetic studies have been limited in both taxon sampling and amount of data. Our objective is to identify clades within Polygonaceae and to provide a global estimate of phylogenetic relationships in this morphologically diverse and geographically widespread group. We include a total of 75 species representing approximately 40 of the 55 named genera in the family. We use three chloroplast regions (rbcL, matK, and ndhF) and the ribosomal internal transcribed spacer to understand the phylogenetic relationships in Polygonaceae. Maximum parsimony and maximum likelihood are used to analyze the data. Symmeria is the sister group to remaining Polygonaceae sampled, and there is strong support for this placement. Afrobrunnichia branches next but has only moderate support. Two large clades comprise Polygonaceae, generally corresponding to those found in previous molecular analyses. Circumscription of most of the currently recognized subgroups within Polygonaceae did not agree with clades identified in the total data analyses, with the exception of Rumiceae Dum.